Laparoscopic spleen-preserving hilar lymph node dissection through pre-pancreatic and retro-pancreatic approach in patients with gastric cancer. Issue 1 (December 2016) - Zheng, Liansheng; Zhang, Ce; Wang, Da; Xue, Qi; Liu, Xiaoping; Zhou, Ke-Jian; Liu, Hao; Li, Guoxin
Abstract Background The conventional radical resection of proximal gastric cancer is even more risky when performed laparoscopically, though this technique is widely used in gastrointestinal surgery and is accepted as the superior method. This paper explores the feasibility of laparoscopic spleen-preserving hilar lymph node dissection using a retro-pancreatic approach for the treatment of proximal gastric cancer. Methods Two cadavers were dissected for examination of and the pre-pancreatic and retro-pancreatic spaces. Following the dissection of the cadavers, ten live patients with proximal gastric cancer from May 2008 to May 2013 at Nanfang Hospital, Guangzhou, China, were given total gastrectomy and adjuvant splenic hilar lymph node clearance through pre-pancreatic and retro-pancreatic approach on the precondition of preserving the pancreas and spleen. The clinicopathologic characteristics, as well as the intraoperative and postoperative variables affecting the procedure, were observed and analyzed. Results Anatomy of the space anterior and posterior to the pancreas in the two cadavers demonstrated the feasibility of pre-pancreatic and retro-pancreatic approach. The surgeries were all successfully performed laparoscopically; conversion to laparotomy was not necessary for any of the ten patients. The overall mean operative time was 243.6 ± 45 min. The mean estimated blood loss was 232 ± 80 ml. At the time of follow-up (median 12 months post-surgery), there had been neither local recurrence nor mortality in any of the patients. Conclusion Laparoscopic spleen- and pancreas-preserving splenic hilar lymph node dissection during total gastrectomy, using both pre-pancreatic and retro-pancreatic approaches, is indicated as a safe and feasible method for the treatment of proximal gastric cancer.